Instrumentation platform and Maximum Power Point tracking control for a hydrokinetic turbine - Mac Donald, Ramasy Rafaël (2017)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2017.